Growth Differentiation Factor 15 Is Associated With Alzheimer’s Disease Risk - Wu, Peng-Fei; Zhang, Xing-Hao; Zhou, Ping; Yin, Rui; Zhou, Xiao-Ting; Zhang, Wan (Frontiers in Genetics, 2021)
Background: Previous observational studies have suggested associations exist between growth differentiation factor 15 (GDF-15) and neurodegenerative diseases. We aimed to investigate the causal relationships between GDF-15 and Alzheimer's disease (AD), Parkinson’s disease (PD), and amyotrophic lateral sclerosis (ALS). Methods: Using summary-level datasets from genome-wide association studies of European-ancestry, we performed a two-sample Mendelian randomization (MR) study. Genetic variants significantly associated (p < 5 × 10−8) with GDF-15 were selected as instrumental variables (n = 5). An inverse-variance weighted method was implemented as the primary MR approach, while weighted median, MR-Egger, leave-one-out analysis and Cochran’s Q test were conducted as sensitivity analyses. All analyses were performed using R 3.6.1 with relevant packages. Results: MR provided evidence for the association of elevated GDF-15 levels with higher risk of AD (OR = 1.14; 95% CI, 1.04–1.24; p = 0.004). In the reverse direction, Mendelian randomization suggested no causal effect of genetically proxied risk of AD on circulating GDF-15 (p = 0.450). Causal effects of GDF-15 on PD (p = 0.597) or ALS (p = 0.120) were not identified; and likewise, MR results did not support the association of genetic liability to PD or ALS with genetically predicted levels of GDF-15. No evident heterogeneity or horizontal pleiotropy were revealed by multiple sensitivity analyses. Conclusion: Altogether, we highlighted the role of GDF-15 in AD as a promising diagnostic marker and therapeutic target.